Participatory Governance Dalam Pemberdayaan Kelompok Tani Di Kelurahan Manggala Kota Makassar - Yanty, Norma; Nasrulhaq, Nasrulhaq; Mahsyar, Abdul (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study purposed to determine participatory governance in empowering farmer groups. The study used  qualitative research, while the informants were 4 people. Data collection techniques with in-depth interviews with a number of informants., Direct observation, documentation. The results of this study showed that the lack of socialization by the government to farmers about the importance of farmer groups, as well as the provision of counseling, understanding in socializing the problem. This was seen from the indicators: (1) Socialization in which the government provided knowledge about the function of the government as a facilitator and mentoring to farmer groups in community empowerment (2) Assistance in the process by which the government carried out both knowledge and technical assistance to the farming community (3) Training- training provided by the government to farmer groups in empowering farmer groups, both providing facilities and knowledge of hazardous materials used by farmers and (4) Field Visits conducted by the local government directly to farmers and carried out directly in the field or in the fields being cultivated by the farming community. Keywords: Participatory Governance, farmer groups